UPAYA MENERAPKAN STANDAR PELAYANAN MINIMAL DI BIDANG KESEHATAN PADA INDIKATOR PELAYANAN KESEHATAN HIPERTENSI DI PUSKESMAS KOTA SEMARANG - Anindya, Prakasita Artha; Jati, Sutopo Patria; Nandini, Nurhasmadiar (Fakultas Kesehatan Masyarakat, 2020)
Minimum Service Standards have to be provided by each region to their citizen regarding the minimum type and quality of basic services. Minimum health service standard have 12 type of basic services. One of them are the health service of hypertension patient which was only 24,75% in 2017 from target 100% in Semarang. The research objective was to analyze the application of minimum service standards. This research used a qualitative method with a descriptive analytic approach. Data collected were primary data from in-depth interviews and secondary data that were relevant to the research needs. The study was conducted at Gunungpati Health Center, Ngesrep Health Center, Pudak Payung Health Center, Sekaran health Center, and Semarang City Health Office with research subjects as Head of Health Center, Head of Administration, Responsible PTM Program Holder, and patients. The results showed the Minister of Health?s Regulation Number 4 of 2019 concerning Minimum Service Standards in the Health sector was too ideal and was it difficult to reached. Puskesmas as the executor of the Minister of Helath Regulation Number 4 of 2019 must have innovations in order to achieve the 100% target.